Manajemen Perencanaan Kepala Dinas Dalam Meningkatkan Pelayanan Publik - Jarsan, Jarsan; Fridiyanto, Fridiyanto (Center for Religious Studies and Social Empowerment Foundation, 2023)
This study reveals the weak analysis of the internal capabilities of the Sarolangun Regency Regional Library and Archives Service in conducting public services. The question in this research is why service planning at the Regional Library and Archives Service of Sarolangun Regency is not optimal. This research uses a qualitative descriptive approach. Data collection was carried out by observation, interview and documentation techniques. The subjects of this study were service heads, service secretaries, ASN employees and visitors. Data analysis techniques were carried out by data reduction, data presentation, drawing conclusions and verifying the reliability of the research results. The results of the study show that public service planning management is structured in the existing policy format, regardless of internal capabilities. The conclusion of this study is that planning management at the Sarolangun Regency Regional Library and Archives Service is not yet optimal because there are many factors that need to be addressed. Penelitian ini mengungkap tentang lemahnya analisis kemampuan internal Dinas Perpustakaan dan Arsip Daerah Kabupaten Sarolangun dalam melakukan pelayanan publik. Pertanyaan dalam penelitian ini adalah mengapa perencanaan pelayanan di Dinas Perpustakaan dan Arsip Daerah Kabupten Sarolangun belum optimal. Penelitian ini menggunakan pendekatan kualitatif bersifat deskriptif. Pengumpulan data dilakukan dengan teknik observasi, wawancara dan dokumentasi. Subjek penelitian ini adalah kepala dinas, sekretaris dinas, pegawai ASN dan pengunjung. Teknik analisis data dilakukan dengan reduksi data, penyajian data, penarikan kesimpulan dan verifikasi keterpercayaan hasil penelitian. Hasil penelitian menunjukkan bahwa manajemen perencanaan pelayanan publik disusun dalam format kebijakan yang ada, tanpa melihat kemampuan internal. Kesimpulan penelitian ini adalah manajemen perencanaan di Dinas Perpustakaan Dan Arsip Daerah Kabupaten Sarolangun belum optimal karena banyak faktor yang perlu dibenahi.